Comparative evaluation of high-pressure processing and enzyme maceration as innovative nonthermal pre-treatments in jaboticaba juice production - Zaman, Nor Azwan Haniff Kamarol; Ijod, Giroon; Nawawi, Nur Izzati Mohamed; Rosli, Nur Addina Mohamad; Hean, Chong Gun; Adzahan, Noranizan Mohd; Azman, Ezzat Mohamad (Codon Publications, 2026)
Jaboticaba (Myrciaria jaboticaba) is a polyphenol-rich fruit, particularly abundant in anthocyanins concentrated within its thick peel, which exhibits potent antioxidant activity. Owing to the thermal sensitivity of these compounds, nonthermal processing techniques, such as high-pressure processing (HPP) and enzymatic maceration, were compared to enhance anthocyanin extraction while minimizing degradation. In this study, whole jaboticaba fruits were subjected to HPP at 400, 500, and 600 MPa for 3, 6, and 10 min, while enzymatic maceration was performed using 0.2% amylase, 0.2% pectinase, and a combination of 0.1% amylase + 0.1% pectinase (v/w) at 50 ± 1°C for 30 min. Treatment with 0.2% amylase significantly (p < 0.05) increased total anthocyanin content, total phenolic content, and antioxidant activity while effectively reducing residual polyphenol oxidase activity. Conversely, HPP at 600 MPa for 6–10 min significantly decreased peroxidase activity, whereas the 400 MPa (3 min) treatment yielded the highest total sugar content. Among the HPP treatments, the highest total anthocyanin content was recorded at 400 MPa, suggesting that moderate pressure, regardless of holding time, enhances anthocyanin release from the fruit matrix. Overall, these findings demonstrate that both HPP and enzymatic maceration are promising nonthermal pre-treatment strategies for improving anthocyanin recovery, antioxidant capacity, and enzymatic stability in jaboticaba juice, thereby contributing to the development of high-quality, minimally processed functional beverages.